Hypertensive Nephropathy: Is Hydrogen Sulfide a Game Changer? - Dugbartey , George J. (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Hypertension is a major public health problem globally. It is the most common cause of cardiovascular morbidities and mortalities, with a negative impact on renal function. Uncontrolled hypertension causes chronic kidney disease, which progresses to end-stage renal disease and eventually loss of renal function. Unfortunately, the mechanism underlying the pathogenesis of hypertension and its associated nephropathy is still poorly understood. Also worrying is the fact that despite conventional antihypertensive therapies, achievement of blood pressure control and preservation of renal function still remain a worldwide public health challenge in a significant subpopulation of hypertensive patients. This suggests the need for novel pharmacotherapeutic approaches to curb the problem. Hydrogen sulfide (H2S), the third established member of the gasotransmitter family after nitric oxide and carbon monoxide, has been recognized and established to possess antihypertensive and renoprotective properties, which may represent an important therapeutic alternative for hypertensive nephropathy. In this chapter, recent findings from preclinical studies about therapeutic effect of H2S against hypertensive nephropathy, and its future clinical use are discussed.